A U-shaped dose-response of carbohydrate-protein supplementation on rowing performance - Wang, X.; Wu, H. (Frontiers in Nutrition, 2025)
Background and aim: Co-ingestion of carbohydrate and protein supplement (CHO-PRO) is a common strategy to enhance endurance performance. However, the optimal dose-response relationship has not been established, which limits evidence-based nutritional guidance for individuals. This study aimed to characterize the performance dose-response curve of a 4:1 CHO-PRO during prolonged rowing.